Temperature dependence of the critical points of monolayer MoS2 by ellipsometry. Issue 7 (8th August 2016) - Park, Han Gyeol; Kim, Tae Jung; Kim, Hwa Seob; Yoo, Chang Hyun; Barange, Nilesh S.; Le, Van Long; Kim, Hyoung Uk; Senthilkumar, Velusamy; Le, Chinh Tam; Kim, Yong Soo; Seong, Maeng-Je; Kim, Young Dong
ABSTRACT: We report the complex pseudodielectric function of molybdenum disulfide (MoS2 ) monolayers for energies from 1.40 to 6.42 eV and temperatures from 35 to 350 K. MoS2 was grown as a continuous monolayer on a SiO2 /Si substrate in a two zone hot-wall furnace using a catalyst-free chemical vapor growth process. The monolayer was then transferred onto a sapphire substrate. We investigated the optical properties of MoS2 using a dual-rotating-compensator ellipsometer with the sample in ultrahigh vacuum to prevent degradation and to minimize condensation artifacts in the data at low sample temperatures. Critical-point (CP) energies were determined using numerically calculated second energy derivatives of the spectra. At low temperature, we observed a splitting of A -excitonic peak. This identifies the bound excitonic states, including negatively charged excitons, trion states in monolayer MoS2 . Splitting of the B -excitonic peak is also indicated. Blue shifts of the CP energies and enhanced structures with reduced electron–phonon interaction are observed as the temperature is lowered. The temperature dependences of the CP energies were fit to a phenomenological expression that contains the Bose–Einstein statistical factor and the temperature coefficient.